Riding (High) into the danger zone: a review of potential differences in chemical exposures in fighter pilots resulting from high altitude and G-forces. (2nd September 2017) - Linakis, Matthew W.; Job, Kathleen M.; Liu, Xiaoxi; Collingwood, Scott C.; Pangburn, Heather A.; Ott, Darrin K.; Sherwin, Catherine M. T.
ABSTRACT: Introduction : When in flight, pilots of high performance aircraft experience conditions unique to their profession. Training flights, performed as often as several times a week, can expose these pilots to altitudes in excess of 15 km ( 50, 000 ft, with a cabin pressurized to an altitude of 20, 000 ft), and the maneuvers performed in flight can exacerbate the G-forces felt by the pilot. While the pilots specifically train to withstand these extreme conditions, the physiologic stress could very likely lead to differences in the disposition of chemicals in the body, and consequently, dangerously high exposures. Unfortunately, very little is known about how the conditions experienced by fighter pilots affects chemical disposition. Areas covered : The purpose of this review is to present information about the effects of high altitude, G-forces, and other conditions experienced by fighter pilots on chemical disposition. Using this information, the expected changes in chemical exposure will be discussed, using isopropyl alcohol as an example. Expert opinion : There is a severe lack of information concerning the effects of the fighter pilot environment on the pharmacokinetics and pharmacodynamics of chemicals. Given the possibility of exposure prior to or during flight, it is important that these potential effects be investigated further.